EU competition law and sector-specific regulation in the converging communications industry - Nikolinakos, NikosTh. (The University of Edinburgh, 2004)
Part I traces the evolution of EU telecommunications policy (from 1987 to 1998) and presents an overview of and commentary on the main provisions of the current EU telecommunications regulatory framework. It discusses the principal policy documents which set the tone for the transition from a monopoly to a fully liberalised market and focuses on both liberalisation and harmonisation legislative measures in the EU.

Part II concentrates on specific abusive behaviour of the incumbents aimed at preserving their key bottleneck positions against newcomers, and examines how competition law can deal with such cases. In particular, it discusses the jurisprudence of the ECJ involving cases of refusal to supply and the European Commission's essential facilities cases, and attempts to define to what extent Article 82 (ex 86) of the Treaty is applicable to the control of bottlenecks. Furthermore, it analyses EU competition policy on the strategic alliances and mergers arising from the accelerating convergence of the telecommunications, media and information technology sectors

Part III examines how the current EU telecommunications regulatory regime should be adapted to the emerging multimedia environment. It concludes that, at least during the transition phase towards the realisation of an effectively competitive market, specific regulation will play a fundamental role alongside competition law. It also assesses the scope and nature of the new regulatory regime in the converging environment and submits that a light-touch and predictable regulatory framework - based on the new commercial realities rather than on arbitrary and obsolete regulatory distinctions - is required. This means that a large majority of the prescriptive regulations currently in place will need to be replaced by a harmonised framework of general principles and overall targets which can identify and monitor barriers to competition within a converging market and can ensure equal and fair conditions for market players.

Part IV comments on the proposed Framework, Access, and Licensing Directives. It attempts to assess whether the forthcoming regulation for electronic communications networks and associated services is in line with the main policy objectives and those regulatory principles that underpin the existing regulatory framework and whose significance has been affirmed in responses to consultation: legal certainty, flexibility, continuity, and transparency.